Determination of vicine and convicine from faba bean with an optimized high-performance liquid chromatographic method. (October 2015) - Pulkkinen, Marjo; Gautam, Maheswor; Lampi, Anna-Maija; Ollilainen, Velimatti; Stoddard, Frederick; Sontag-Strohm, Tuula; Salovaara, Hannu; Piironen, Vieno
Abstract: A robust method was implemented to analyze vicine and convicine from faba bean and used to study variation among cultivars and growing years. Due to the different solubilities and stabilities of vicine and convicine, two extraction methods were compared, and conditions for high-performance liquid chromatography (HPLC) were optimized. The chosen method consisted of extraction with 7% perchloric acid with uridine as an internal standard, separation with a C18 column using 0.1% formic acid in water as the mobile phase, and UV detection at 273 nm. The response factors of vicine and convicine relative to uridine were determined using purchased vicine and convicine that was isolated from faba bean fractions by a preparative liquid chromatographic (LC) system coupled with mass spectrometry (MS). The established factors for vicine and convicine were 1.53 and 1.63, respectively. Their similarity makes it possible to use vicine as a standard for quantification of convicine in the absence of a convicine standard and vice versa. Among 10 cultivars grown in the same year and location, vicine and convicine concentrations ranged from 5.2–7.6 mg/g dw and 2.1–3.6 mg/g dw, respectively. Variation among growing years was relatively small but statistically significant (P < 0.05). Highlights: A robust method for vicine and convicine analysis was introduced. Relative response factors for vicine and convicine to uridine were established. Variation was more marked among cultivars than among growing years.